Intellectual Capital and Profitability Performance: Empirical Evidence on Basic and Chemical Industry Companies on the Indonesia Stock Exchange - Elizar Sinambela; Annisa Cerollin (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Intellectual capital is often not directly recorded on the balance sheet, even though its information is used to create value, competitive advantage, and improve company performance. This study aims to analyze the effect of intellectual capital on profitability performance in basic and chemical industry companies listed on the Indonesia Stock Exchange. Intellectual capital is measured using the Value Added Intellectual Coefficient (VAIC™) approach, which consists of Value Added Human Capital (VAHU), Value Added Capital Employed (VACA), and Structural Capital Value Added (STVA), while profitability is proxied by Return on Assets (ROA). With a quantitative approach, this study uses secondary data in the form of company financial reports obtained from the official website of the Indonesia Stock Exchange. The sampling technique used purposive sampling with a sample size of 10 companies over a six-year period, resulting in 60 observations. Data analysis methods using descriptive statistics and multiple linear regression analysis to test the research hypothesis. The results of the study indicate that VAHU, VACA, and STVA partially significantly influence ROA. Furthermore, these three intellectual capital components simultaneously significantly influence company profitability. These findings indicate that effective intellectual capital management plays a crucial role in improving the financial performance of basic and chemical industry companies